ISTmobil: Customer needs orientated, individual mobility services in suburban areas (Individual Mobility as a Service). - Fürdös, Alexander; Sager, Thomas; Brunner, Stefan; Stiasny, Alexander (My University, 2018)
Der Grundgedanke des ISTmobil-Konzepts ist die Schaffung von Mikro-ÖPNV-Systemen für ländliche und vorstädtische Gebiete, die mit dem bestehenden ÖPNV-Angebot verbunden sind.

January 2014, challenges concerning urban mobility worldwide and strategies for cities to shape urban mobility better are identified (Arthur D. Little, UITP (2014)). The study indicates that in most cities the potential of urban mobility measures is not achieved and most cities are still badly equipped to cope with the challenges ahead. According to the Arthur D. Little study developements toward individualization and sustainability will require mobility services portfolio extension as well as business model transformation (Arthur D. Little, UITP (2014)). So the developement of urban mobility systems that are able to respond to this challenges is one of the greatest challenges facing cities today. Connection ISTmobil and Urban Mobility Initially the concept of ISTmobil was developed for rural or sub-urban areas. These areas are often characterized by marginal public transport supply. In some cases inhabitants and visitors depend on the private car and have no other choice. One aspect which is linked to this problem is the high rate of motorization within the communities. Looking at the initial situation and the urbanisation trend, which forces people from rural areas to commute in urban areas, there is also a connection to the topic urban mobility. In order to strengthen the use of public transport systems and at the same time mitigating commuting flows of motorised individual transport in the cities the ISTmobil system was developed. Therefore a special offer for commuters, the so called Pendlerabo , was developed. The ISTmobil concept The underlying idea behind the concept ISTmobil is the creation of micro public transport systems for rural and suburban areas which are cross-linked to exisiting public transport supply. Moreover, it should be possible to travel in a region or in near future in the whole country with one card and one booking number. A One-stop shop supply of complete mobility services would ease the usage of the mobility services. Another important aspect is to foster cooperations and increase coordination of the different mobility services, which leads to the pooling of regional transport providers.
Keywords: Ländlicher Raum; Stadtumland; Regionalverkehr; Individualverkehr; Verkehrsverbund; ÖPNV; Verkehrsbedarf; Bedarfsorientierung; Nachfrageorientierung; Rufbus